Current state and future directions of the National Board of Chiropractic Examiners - Ouzts, Norman E. (J Chiropr Educ, 2020)
The objective of this paper is to describe changes made to chiropractic national board examinations in the United States, including methodologies in test scoring, and to discuss future directions in test development and administration being considered by the National Board of Chiropractic Examiners (NBCE). Additionally, this paper serves as an introduction to the articles written by the NBCE staff and published in this issue of the journal. Statistical perspective on the properties of a test are presented, and reasons for the NBCE moving to item response theory for test scoring are described. NBCE consideration of on-demand testing and changes implemented in the Part IV practical examination are also discussed.